Role of Bangabandhu in expanding higher education and Bangladesh today - Khan, Hafiz T.A. (Journal of Economic Development, Environment and People, 2021)
The study attempts to evaluate the role of Bangabandu Sheikh Mujibur Rahman, the Founding Father of Bangladesh, in his initial plan on higher education and to produce adequate human resources to rebuild the country since independence. Secondary sources of information are used to evaluate his role in higher education expansion in Bangladesh. It has been revealed that the economic growth and development seen in Bangladesh today was largely impacted by his education plan.